2019
DOI: 10.1155/2019/6459498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimalarial Activity of the Leaf Latex and TLC Isolates from Aloe megalacantha Baker in Plasmodium berghei Infected Mice

Abstract: Malaria is a devastating parasitic disease which caused around 216 million cases and 445,000 deaths worldwide in 2016. This might be attributed to a wide spread of drug resistant parasites. The plant Aloe megalacantha is indigenous to Ethiopia where the sap of the leaves is traditionally used for the treatment of malaria. This study was aimed at evaluating the antimalarial effect of leaf latex and isolates obtained from Aloe megalacantha against chloroquine sensitive Plasmodium berghei ANKA strain in Swiss alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
7
18
0
Order By: Relevance
“…The relative variation in parasite suppression activity among doses might be due to variation in the amount of secondary metabolites contents in the leaf latex of Aloe weloensis. This show that Aloe weloensis is endowed with a very good antimalarial activity and concordant to promising antimalarial activity of Aloe vera, Aloe pulcherrima and Aloe megalacantha in the genus Aloe (19)(20)(21). In another studies, signi cant dose-dependent parasite suppression was demonstrated after administration of Aloe macrocarpa, Aloe debrana and Aloe sinana which indicate a promising antimalarial activity and providing the scienti c evidence for the folkloric use of the plant (41,42).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The relative variation in parasite suppression activity among doses might be due to variation in the amount of secondary metabolites contents in the leaf latex of Aloe weloensis. This show that Aloe weloensis is endowed with a very good antimalarial activity and concordant to promising antimalarial activity of Aloe vera, Aloe pulcherrima and Aloe megalacantha in the genus Aloe (19)(20)(21). In another studies, signi cant dose-dependent parasite suppression was demonstrated after administration of Aloe macrocarpa, Aloe debrana and Aloe sinana which indicate a promising antimalarial activity and providing the scienti c evidence for the folkloric use of the plant (41,42).…”
Section: Discussionsupporting
confidence: 54%
“…The latex of Aloe weloensis leaf showed antibacterial effect against gram negative and gram positive strains (17). The leaf latex of the plant has been used in folk medicine against malarial and others human ailment in Ethiopia (18).The leaf latex and isolated compounds of Aloe vera, Aloe pulcherrima and Aloe megalacantha, a similar plant species, possessed signi cant antimalarial activity (19)(20)(21).As a result, Aloe weloensis may have similar effect as all plants belong to the same genus. Therefore, the current study was aimed to investigate antimalarial activity of the leaf latex of Aloe weloensis.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia there are around 46 species of Aloe, of which about 66% are endemic in the country [8]. Several of these endemic species possessed different biological activities, including antimicrobial [9,10], antitrypanosomiasis [11], antileishmaniasis [12,13], antimalarial [14][15][16], wound healing [17], anti-inflammatory [17,18], anticancer [19], antidiabetic [20], and antioxidant activities [21]. is relevance indicates that Aloe is the store house of numerous bioactive compounds [22].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf latexes of both A. elegans and A. monticola were collected and dried as per the method described and were considered as an extract [1,13]. The leaf of H. schulli and the roots of C. tomentosa and T. gracilipes were dried under shaded open air.…”
Section: Preparation Of the Extractsmentioning
confidence: 99%
“…Beyond 80% of the global population are heavily using traditional medicines, commonly plant-based medicines, for management of numerous types of illnesses including malaria [1]. Malaria is an infectious disease caused by the parasites belonging to Plasmodium genus with P. falciparum causing the most life-threatening type of malaria [2].…”
Section: Introductionmentioning
confidence: 99%